Cephalic Vein Intravascular Foreign Body After a Penetrating Injury: A Case Report. Issue 4 (27th October 2022) - Stark, Michael; Matzon, Jonas L.
Abstract : Case: A 65-year-old man presented with a right forearm metallic foreign body after a projectile injury while using a table saw. The area in question appeared infected prompting a surgical incision and drainage. In the operating room, the metallic foreign body was noted to be entirely intravascular within the lumen of the cephalic vein. It was ultimately removed, and the patient recovered without complication. Conclusion: Although foreign bodies after traumatic injury are common, it is exceedingly rare to encounter an intravascular foreign body. However, the consequences of proximal migration can be devastating and thus should be in the differential diagnosis for all treating surgeons.